The Role of Aswaja Values in Enhancing the Professional Ethics of Notaries in Indonesia - Agustan, Fajar (University of Darusssalam Gontor, 2025)
This research discusses the influence of Aswaja values on the professional ethics of notaries in Indonesia. The professional ethics of notaries, derived from the Greek word